Association between MTHFR polymorphisms and vitamin D status in infertile women: a mediation analysis - Zhou, Ruiqiong; Zhu, Zhenghong; Wang, Zhaoyi; Dong, Mei; Huang, Li; Wang, Songlu; Zhang, Xiqian; Liu, Fenghua (Frontiers in Nutrition, 2025)
BackgroundMethylenetetrahydrofolate reductase (MTHFR) regulates folate metabolism and homocysteine (Hcy) methylation. Impaired folate metabolism and vitamin D deficiency are both closely associated with female reproductive disorders, but their specific roles and relationship remain largely unknown. This study aimed to investigate the relationship between MTHFR polymorphisms and vitamin D status and to examine the mediating effect of Hcy.MethodsA total of 6,344 infertile patients were included in this retrospective study. Multivariable logistic regression and multiple linear regression models, and stratified analyses were used to investigate the relationship between MTHFR polymorphisms (C677T and A1298C) and vitamin D status. Smooth curve fitting model and spearman correlation analysis were used to explore the correlation between Hcy levels and vitamin D status. Mediation analyses were performed to examine the direct and indirect effects of MTHFR polymorphisms on vitamin D status.ResultsThe risk of vitamin D deficiency and serum Hcy levels were significantly higher in patients with MTHFR677CT and TT compared with CC (p < 0.001 for both). In multivariate regression models, MTHFR677CT and TT were positively associated with vitamin D deficiency compared with CC. No significant differences were found for A1298C polymorphism. Smooth curve fitting models showed that serum Hcy was linearly correlated with both 25(OH)D levels (p-nonlinear = 0.063) and prevalence of vitamin D deficiency (p-nonlinear = 0.261). In mediation analyses using logistic regression models, Hcy mediated 15.8 and 41.6% of the associations between 677CT and TT (versus CC) and vitamin D deficiency, respectively.ConclusionThe effect of C677T polymorphism on vitamin D status can be explained jointly by a direct association between C677T polymorphism and vitamin D, and an indirect association mediated by Hcy.